Modeling Steel Corrosion Failure in Reinforced Concrete by Cover Crack Width 3D FEM Analysis - Castorena-González, J. H.; Martin, U.; Gaona-Tiburcio, C.; Núñez-Jáquez, R. E.; Almeraya-Calderón, F. M.; Bastidas, J. M.; Bastidas, D. M. (Frontiers in Materials, 2020)
A new predictive 3D FEM model is proposed using the corrosion damage function by measuring the concrete cover crack width, which is a function of the free concrete cover depth, the steel rebar diameter, the mechanical properties of the concrete, and the length of the anodic zone. A significant aspect to evaluate service lifetime conditions in corroded reinforced concrete structures (RCS) is the concrete cover crack width. Surface cracks originate due to the pressure exerted by the volume expansion of the corrosion products and oxide layer formed on the rebars. In this work, concrete cover crack width on corroded RCS is analysis by means of finite element method allowing a corrosion damage model to be proposed. The model obtained was used to find a theoretical relationship between the dissolved steel (corrosion process) and the concrete cover crack width. The results were validated using three experimental data sets from the literature: two corrosion case studies in natural environments and one work covering accelerated corrosion in laboratory test conditions. All the beams were exposed to the simultaneous action of flexural stresses and corrosion. A good correlation was observed between the model and the experimental results, thus supporting reliability of the analytical process and validation of the proposed corrosion damage model.